ARTIFICIAL INTELLIGENCE IN FINANCIAL RISK MANAGEMENT: INNOVATIONS AND CHALLENGES - Bakoeva Gulbakhor (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
This article examines how Artificial Intelligence (AI) is reshaping financial risk management by transforming the way financial institutions identify, assess, and mitigate risks. The paper explores key innovations, such as machine learning (ML), natural language processing (NLP), and predictive analytics, which enable institutions to anticipate market volatility, detect fraud, and enhance credit risk assessment. Additionally, it discusses critical challenges, including algorithmic bias, data quality, cybersecurity, and regulatory uncertainty. The study concludes that while AI offers unprecedented capabilities in improving financial decision-making and stability, effective governance and ethical frameworks are essential for sustainable implementation.